2023
DOI: 10.1002/mnfr.202200348
|View full text |Cite
|
Sign up to set email alerts
|

MicroRNA‐29a Compromises Hepatic Adiposis and Gut Dysbiosis in High Fat Diet‐Fed Mice via Downregulating Inflammation

Abstract: Scope: miR-29a expression patterns influence numerous physiological phenomena. Of note, upregulation of miR-29a ameliorates high-fat diet (HFD)-induced liver dysfunctions in mice. However, the miR-29a effect on gut microbiome composition and HFD-induced gut microbiota changes during metabolic disturbances remains unclear. The study provides compelling evidence for the protective role of miR-29a in gut barrier dysfunction and steatohepatitis. Methods and results: miR-29a overexpressed mice (miR-29aTg) are bred … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 77 publications
0
0
0
Order By: Relevance
“…41 At the genus level, TP also enhanced the abundance of Muribaculaceae , Bifidobacterium and Candidatus_Saccharimonas and reduced the abundance of Lactobacillus , Lachnospiraceae_NK4A136_group and Romboutsia , where most of these bacteria were reported to be prominently disordered in patients with adiposis. 6,14,42 For example, Li et al reported the modulatory effects of Tyrosol from olive oil on BAT thermogenesis and WAT browning, which was associated with the increased relative abundance of Muribaculaceae and Lachnospiraceae_bacterium_28_4 and a lowered ratio of Firmicutes to Bacteroidetes . 43 Fu Brick Tea polysaccharides activated BAT by regulating SCFAs, accompanied by enhanced relative abundances of Parabacteroides , Akkermansia , and Bifidobacterium .…”
Section: Discussionmentioning
confidence: 99%
“…41 At the genus level, TP also enhanced the abundance of Muribaculaceae , Bifidobacterium and Candidatus_Saccharimonas and reduced the abundance of Lactobacillus , Lachnospiraceae_NK4A136_group and Romboutsia , where most of these bacteria were reported to be prominently disordered in patients with adiposis. 6,14,42 For example, Li et al reported the modulatory effects of Tyrosol from olive oil on BAT thermogenesis and WAT browning, which was associated with the increased relative abundance of Muribaculaceae and Lachnospiraceae_bacterium_28_4 and a lowered ratio of Firmicutes to Bacteroidetes . 43 Fu Brick Tea polysaccharides activated BAT by regulating SCFAs, accompanied by enhanced relative abundances of Parabacteroides , Akkermansia , and Bifidobacterium .…”
Section: Discussionmentioning
confidence: 99%
“…The miR-29a family has been recognized as a pleiotropic molecule that serves various physiological functions. Our previous research discussed the expression and regulation mechanism of miR-29a in various diseases, such as liver injury/fibrosis [44,45], diabetic nephropathy [21], osteoarthritis [46], and rotator cuff lesion [40], etc., and has proven that miR-29a significantly affects the expression of IL-6, TGF-β, Dnmt3b [47], TNFSF13b [26], FoXO-3 [48], COL3A1 [49], and more [50]. Regardless, ubiquitous expression of miR-29a has systemic regulation and a beneficial impact on various pathological processes throughout the body.…”
Section: Discussionmentioning
confidence: 99%